Advanced interatrial block precedes atrial fibrillation and stroke. The prospective interatrial Block And Yearly EventS (BAYES) registry. (25th November 2020) - Martinez-Selles, M; Elosua, R; Ibarrola, M; De Andres, M; Diez-Villanueva, P; Bayes-Genis, A; Baranchuck, A; Bayes De Luna, A
Abstract: Background: Advanced interatrial block (IAB), prolonged and bimodal P waves in surface ECG inferior leads, is an unrecognized surrogate of atrial dysfunction and a trigger of atrial dysrhythmias, mainly atrial fibrillation (AF). Our aim was to prospectively assess whether advanced IAB in sinus rhythm precedes AF and stroke in elderly outpatients with structural heart disease, a group not previously studied. Methods: Prospective observational registry that included outpatients aged ≥70 years with structural heart disease and no previous diagnosis of AF. Patients were divided into three groups according to P-wave characteristics. Results: Among 556 individuals, 223 had normal P-wave (40.1%), 196 partial IAB (35.3%), and 137 advanced IAB (24.6%). After a median follow-up of 694 days; 93 patients (16.7%) developed AF, 30 stroke (5.4%), and 34 died (6.1%). Advanced IAB was independently associated with AF (hazard ratio [HR] 2.9, 95% confidence interval [CI] 1.7–5.1, p<0.001), stroke (HR 3.8, 95% CI 1.4–10.7, p=0.010), and AF/stroke (HR 2.6, 95% CI 1.5–4.4, p=0.001). P-wave duration (ms) was independently associated with AF (HR 1.05, 95% CI 1.03–1.07, p<0.001), AF/stroke (HR 1.04, 95% CI 1.02–1.06, p<0.001), and mortality (HR 1.04, 95% CI 1.00–1.08, p=0.021). Conclusions: The presence of advanced IAB in sinus rhythm is a risk factor for AF and stroke in an elderly population with structural heart disease and no previous diagnosis of AF. P-wave duration was also associated with all-cause mortality. Figure. Age- and sex-adjusted linear and non-linear association between P-wave duration (msec) and atrial fibrillation (A), stroke (B), and atrial fibrillation or stroke (C) risk. Results of a generalized additive model with spline smoothing functions and 4 degrees of freedom. Funding Acknowledgement: Type of funding source: None